ANALISA DAYA DUKUNG PONDASI TIANG PANCANG BETON PADA PROYEK PEMBANGUNAN RUMAH SAKIT DI KABUPATEN DELI SERDANG - Winarti Winarti; Kartika Indah Sari (Jurnal Teknik Sipil, 2022)
A building structure consists of an upper structure and a lower structure. The superstructure includes beams, plates, columns, as well as the roof and the lower structure is the foundation. Before carrying out a construction, the first thing that is carried out and carried out in the field is the work of the sub-base foundation, which is a foundation construction between the foundation and the pile foundation. Pile foundations are relatively long and slender rods used to support loads on soil layers with low bearing capacity. The purpose of this study is to determine the depth and strength of the soil layer strength. To determine the cone penetration (penetration of the cone tip expressed in the unit area force).To determine the amount of soil adhesive resistance (soil resistance or soil friction against the biconus sheath expressed in the unit length force). The results obtained from the results of this manual calculation, the authors found that the largest bearing capacity of the foundation was 78.73 t/m-2. So it can be concluded from the results obtained from this calculation which means that the greater the cross-sectional area or diameter of this pile, the greater the bearing capacity that the foundation can withstand and the longer the pile, the greater the bearing capacity that can be endured. from that foundation.